Investigating factors influencing sustainable development, performance, and delivery processes of green construction projects in south africa - Singata, Palesa (Department of Construction Economics and Management, 2024)
The construction industry has taken a step towards the implementation of green buildings to reduce the negative environmental impact of buildings and to achieve sustainable development. Green building certification is gaining traction globally and in South Africa. It has become a requirement for some private and government-owned buildings. Even though green certification is still voluntary, it is desired that more buildings obtain the green certification to measure environmental sustainability performance during the different phases of the building's lifecycle. However, there is limited research on the factors that influence the quest for the development of sustainable buildings in South Africa. Therefore, this research evaluates critical factors influencing sustainable development, performance, and delivery processes of green construction projects in South Africa. A comprehensive literature review was conducted to identify the factors influencing the development of green construction projects. Thereafter, a questionnaire survey was developed based on these factors. The targeted population for this study were Green Star accredited professionals who are registered with the Green Building Council of South Africa (GBCSA). This study employed cluster random sampling to divide the entire population into geographical regions that contribute to green infrastructure development. The questionnaire was administered online to 97 Green Star accredited professionals who reside within the Gauteng and Western Cape provinces. The data collected were analysed by means of descriptive and inferential statistics. The study revealed that the top ten factors influencing sustainable development, performance, and delivery processes of green construction projects in South Africa are: energy efficiency; water conservation; health and safety in the workplace; enforcement of green building codes and regulations; expressed interest from clients; effective stormwater management; an effective waste management plan for waste diverted to landfills; effective communication and engagement among project stakeholders; professional knowledge and experience in green buildings; and benefits of green buildings techniques. It also emerged that there is a significant relationship between these factors, sustainable development, and the sustainability performance of green construction projects. Based on these findings, the study concludes that clients and project stakeholders with knowledge of the factors influencing the development of green buildings are likely to develop green and sustainable projects. KEY WORDS: Green building, green construction, Green Star, project delivery process, sustainable development, sustainable construction, sustainability performance